Discovering geographic services from textual use cases - Saldaño, Viviana E. (2010)
Component Based Software Development (CBSD) relies upon utilization of previously developed software components OTS (Off-The-Shelf), which are appropriately merged to satisfy particular system requirements. However, wide acceptance of this paradigm at industry requires efficient component identification and selection, aspects which are being investigated until now. In this context, this paper further explores the use of a geographic services taxonomy, which facilitates component identification, and is used by analysts in charge of developing a Geographic Information System (GIS) employing a CBSD approach. In this article, different knowledge extraction techniques are evaluated and a methodology is proposed to standardize resultant vocabulary in order to allow automatic tools to support GIS services search.